تأثير منهج تعليمي باستخدام بعض وسائل المساعدة في تعلم الضربة الامامية و الخلفية المستقيمة للمبتدئات بكرة الطاولة - أحمد, جيهان محمد; صالح, أ.م.د زانا محمد محمد (Sulaimani Journal for Humanities, 2021)
-The researcher has depended on the experimental programme which was suitable with the nature of the research. And research sample was consisted of 14 teenagers from Koya Sports and Youth Center in 2019. Research Hypothesis and Assumptions 1. Having discrepancies in statistical deviation between the introductory and final testing in learning the front and back rightness shoot and developing the rapidity of moving reaction for the tester group. 2. Having discrepancies in statistical deviation between the introductory and final testing in learning the front and back rightness shoot and developing the rapidity of moving reaction for the constant group. 3. Having discrepancies in statistical deviation between the introductory and final testing in learning the front and back rightness shoot and developing the rapidity of moving reaction for the tester and constant group. The Research Methodologies The researcher has depended on the experimental programme which was suitable with the nature of the research. And research sample was consisted of 14 teenagers from Koya Sports and Youth Center in 2019. Many apparatuses, equipments, questionnaire used as a data collection process and applied in this research with a learning programme for the equalization of the two groups of samples. Many statistical methods have been applied in this research such as, median, standard deviation, percentages and coefficient of correlation. The 4th topic included the presentation of results, the statistical remediation process, classification and categorization and creating a database for protecting the data. Later, the discussion of the results and making citations and references for the research has accomplished the main objectives of the research In conclusion: 1- the learning programmes had a positive effect in learning to hit in the form and back by using the helpful elements by the teenagers. 2- the applicated programme had a positive effect in learning to hit in the forn and back by using the helpful elements. 3- the tested groups who applicated the programme and used the helpful elements was more successful than the mixed group in learning to hit at the front and back by the teenagers. 4- both groups were the same in the development of rate to the response movement by teenagers. In recommendation: 1- ensure using the learning elements that have a possiteve effect in learning to hit at the front and back in table tennis. 2- ultimately refusing to give up the obscurity because of some significaut cases in learning like hitting in the front and back at the table tennis. 3- the need of taking care of the development of the rate of response movement thus
Keywords: Tennis; back rightness; front rightness